Syncytia formation by SARS‐CoV‐2‐infected cells - Buchrieser, Julian; Dufloo, Jérémy; Hubert, Mathieu; Monel, Blandine; Planas, Delphine; Rajah, Maaran Michael; Planchais, Cyril; Porrot, Françoise; Guivel‐Benhassine, Florence; Van der Werf, Sylvie; Casartelli, Nicoletta; Mouquet, Hugo; et al. (The EMBO journal, 2020)
Severe cases of COVID‐19 are associated with extensive lung damage and the presence of infected multinucleated syncytial pneumocytes. The viral and cellular mechanisms regulating the formation of these syncytia are not well understood. Here, we show that SARS‐CoV‐2‐infected cells express the Spike protein (S) at their surface and fuse with ACE2‐positive neighboring cells. Expression of S without any other viral proteins triggers syncytia formation. Interferon‐induced transmembrane proteins (IFITMs), a family of restriction factors that block the entry of many viruses, inhibit S‐mediated fusion, with IFITM1 being more active than IFITM2 and IFITM3. On the contrary, the TMPRSS2 serine protease, which is known to enhance infectivity of cell‐free virions, processes both S and ACE2 and increases syncytia formation by accelerating the fusion process. TMPRSS2 thwarts the antiviral effect of IFITMs. Our results show that SARS‐CoV‐2 pathological effects are modulated by cellular proteins that either inhibit or facilitate syncytia formation. Cells infected with SARS‐CoV‐2 fuse with neighboring cells to form syncytia. This process is accelerated by the TMPRSS2 protease and restricted by interferon‐induced transmembrane proteins (IFITMs). SARS‐CoV‐2‐infected cells can fuse with neighboring cells to form syncytia. IFITM proteins, particularly IFITM1, restrict syncytia formation. TMPRSS2 protease accelerates syncytia formation and reverts the inhibitory effects of the IFITMs. Graphical Abstract Cells infected with SARS‐CoV‐2 can fuse with neighbouring cells in a process accelerated by infectivity‐enhancing host factor TMPRSS2 and restricted by antiviral IFITM proteins.